Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1038/sj.ijo.0801513
|View full text |Cite
|
Sign up to set email alerts
|

Trends in BMI among Belgian children, adolescents and adults from 1969 to 1996

Abstract: OBJECTIVE:To document secular data on changes in the distribution of body mass index (BMI), to determine the probability of overweight at 40 y of age in Belgian males in relation to the presence or absence of overweight at different ages in adolescence, and to estimate tracking of BMI in Belgian males in Belgium aged 12 ± 40 y. DESIGN: Cross-sectional and mixed longitudinal surveys in nationally representative samples of Belgian males and females. SUBJECTS: Cross-sectional Ð more than 21 000 boys and 9698 girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 14 publications
10
51
1
Order By: Relevance
“…In most studies, the lower part of the BMI distribution has been found to remain unchanged. In the upper BMI range, although, it has been seen that there is a similar pattern of increase among other populations (Troiano and Flegal, 1998;Hulens et al, 2001). In Aachen (former western part of Germany), between 1966 and 1999, a BMI increase was observed in preschool children.…”
Section: Discussionmentioning
confidence: 62%
“…In most studies, the lower part of the BMI distribution has been found to remain unchanged. In the upper BMI range, although, it has been seen that there is a similar pattern of increase among other populations (Troiano and Flegal, 1998;Hulens et al, 2001). In Aachen (former western part of Germany), between 1966 and 1999, a BMI increase was observed in preschool children.…”
Section: Discussionmentioning
confidence: 62%
“…24 Secular and socio-occupational variation in BMI S Kozieł et al 27 Overweight and obesity in late adolescence tend to track into adulthood. 28,29 Although the prevalence of obesity is low in young adult Polish males, a continued increase in prevalence has the potential for an increase in obesityrelated health consequences.…”
Section: Secular and Socio-occupational Variation In Bmi S Kozieł Et Almentioning
confidence: 99%
“…In the United States, the prevalences of overweight in children and adolescents have doubled and almost tripled respectively since the 1960s. 1 These trends have been observed in all parts of the worldFin affluent societies [2][3][4][5] as well as in developing countries. 6 However, most previous studies have used different definitions of childhood obesity, and thus reported trends were difficult to compare internationally.…”
Section: Introductionmentioning
confidence: 99%